Knowledge‐Driven Design and Lab‐Based Evaluation of B‐doped TiO2 Photocatalysts for Ammonia Synthesis. Issue 8 (1st January 2023) - Liu, Chuangwei; Hao, Derek; Ye, Jin; Ye, Sheng; Zhou, Fengling; Xie, Hongbo; Qin, Gaowu; Xu, Jiating; Liu, Jian; Li, Song; Sun, Chenghua
Abstract: The room‐temperature nitrogen reduction reaction (NRR) is of paramount significance for both the fertilizer industry and fundamental catalysis science. To produce ammonia from water, air, and sunlight, the photocatalytic NRR is targeted to significantly release the energy and environmental pressure associated with the current Habor–Bosch process. In this context, herein, the knowledge‐driven design of boron‐doped TiO2 is demonstrated as a photocatalyst for the nitrogen reduction reaction. Among 54 catalysts in the reported library, anatase TiO2 (101) modified by boron doping is identified as an exceptional NRR catalyst with strong visible‐light absorption (bandgap 1.92 eV) and excellent reactivity with a small thermodynamic barrier (0.44 eV) as well as a high turnover frequency (1.08 × 10 −5 s −1 site −1 ). Experimentally, the predictions of this work are validated using a B‐doped TiO2 nanosheet, achieving ammonia production with a yield of 3.35 mg h −1 g −1 under simulated sunlight irradiation, which significantly renews the performance record for Ti‐based photocatalyst for the NRR. This work highlights the importance of dual active site catalysts for nitrogen activation and reduction and demonstrates the capacity of knowledge‐driven catalyst design. Abstract : A dual active Ti–B site photocatalyst is proposed and validated for photocatalytic ammonia synthesis by combined computational and experimental work. The calculation results show that the defective anatase TiO2 nanosheet doped by boron demonstrates high nitrogen reduction reaction (NRR) selectivity and excellent NRR performance. The 2 wt% B‐doping has the narrowest bandgap. Further experiments are carried out to synthesize the B‐doped nanosheet and provide outstanding ammonia synthesis performance.